Enhancing Students’ Critical Thinking Skills through Problem Based Learning Integrated with Mindmapping - Soleh Ritonga; Kharina Areeisty; Zulkarnaini Zulkarnaini (Universitas Syiah Kuala, 2021)
The critical thinking skills of class 10th from senior high school Banda Aceh students have not been trained in the learning process, students are not given the opportunity to analyze a problem, identify, conclude or come up with new ideas or an action on a problem. In fact, research shows that the learning process of biology in schools does not encourage students to think critically, thus affecting low learning outcomes. The research objective was to determine the increase in critical thinking skills in class 10th skills on the concept of environmental pollution and knowing the differences in critical thinking skills of class 10th students on the concept of environmental pollution in the experimental and control class. Data were collected from March to April 2019. The approach of this research is to use a quantitative, evaluation research type, the method used is quasi-experimental, with a factorial design group pre-test post-test. The sample in this study amounted to 253 students from two high schools in Banda Aceh. Essay questions are used to measure students' critical thinking skills. The data analysis used ANCOVA at a significant level of 0.05. Hypothesis test results show the value of ρ α, 0.00 0.05. The conclusion of this study is that the application of the PBL integrated with the mindmap can improve students' critical thinking skills. There are differences in students' critical thinking skills using integrated mindmapping PBL, PBL, mindmapping, and conventional.